IMPROVING METACOGNITIONAL ABILITIES IN LEARNING MATHEMATICS THROUGH SIMPLE NUMBER OPERATIONS IN EARLY CHIDREN AT RA AL-HUDA WAJAK-MALANG - Kholik Kholik (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
The mathematics learning of early childhood education will be used in the theme of simple number operations. To be applied in everyday life. Mathematics has. The purpose of the study is to describe metacognitive abilities in mathematics learning through simple number operations. The research methodology used is classroom action research (Action Research) using observation data, interviews, and documentation and classroom actions through two cycles including cycle I and cycle II for six meetings. The results and discussion of the study found the importance of mathematics learning by designing appropriate learning strategies. Learning strategies are related to learning techniques that will be presented such as mathematics learning techniques using creative and innovative games. It is proven that the overall data analysis on the average pre-cycle results reached 55% with the technique of recognizing numbers orally. Then, the cycle at the first meeting achieved an average result of 71.25% with a learning concept that combines story problems and playing number classification with number symbols. The results of the cycle at the second meeting achieved an average result of 77.5% with the concept of learning to arrange symbolic numbers and guess numbers and number symbols. Meanwhile, the cycle's third meeting achieved 89.5% success rate, incorporating the concept of learning mathematics through memory circuit games and learning mathematics through an outdoor setting. This demonstrates the success of children's critical thinking skills through stages of understanding supported by innovative and creative learning strategies. Metacognitive skills, as a form of critical problem-solving, contribute to the realization of the concept of enjoyable mathematics learning.